Gender differences in managers' attitudes towards employees with depression: a cross-sectional study in Sweden - Ilaria Mangerini; Monica Bertilsson; Angelique de Rijk; Gunnel Hensing (BMC, 2020)
Abstract Background Depression is prevalent among employees and a major reason for sickness absence. First-line managers' attitudes towards employees with depression might influence return to work and the scant literature indicates gender differences in attitudes. The objective of this study was to investigate gender differences in managers' attitudes to employees with depression. Methods A cross-sectional study was conducted among 4737 Swedish managers in 2017 (response rate 71%, n = 3358). Attitudes towards depression were measured with the instrument "Managerial stigma towards employees with depression" (12 items). The response patterns of women and men, the level of stigma and the direction of the gender differences were investigated with independent t tests and binary logistic regression analyses with covariates. Results The likelihood of reporting high negative attitudes (score ≥ 36) was lower among women than men (odds ratio, 1.64; 95% confidence interval, 1.28-2.10) after adjusting for age, level of education, work sector, distribution of women and men among the staff, current workplace experience in management, lifetime experience in management, managerial position and presence of staff members at the current workplace who had depression and/or anxiety disorders. Conclusions Based on these findings, a gender-sensitive approach is suggested for future interventions to improve managers' attitudes towards employees with depression and other mental disorders.